Review on Rasasindura A Mercurial preparation of Indian System of Medicine - Rohit Ajith Gokarn, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Review on Rasasindura A Mercurial preparation of Indian System of Medicine